Penanaman Nilai-Nilai Agama, Filosofi, Psikologis dan Sosiologis dalam Pembentukan Karakter Siswa di SMP Negeri 21 Kota Tangerang Selatan: Studi Kasus di SMPN 21 Kota Tangerang Selatan - Munandar, Aris; Jamilah Muryati; Naufal Hilmizen; Endang Koswara (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to find information about the habit of strong religious and moral values, good philosophical and psychological understanding, and deep sociological understanding. The method used is a qualitative approach and data collection is through interviews, document review and observation at the research site. At SMPN 21, South Tangerang City, familiarization with religious values ​​includes: 5S (Smile, Greetings, Greetings, Polite and polite), congregational duha prayers, wirid and group prayers, reading verses of the holy Qur'an, cults by students , hadroh by students, clean Jum'ah, Friday prayers, while female students at the same time carry out female activities in the hall by female teachers and ustadah from outside. Then the school also commemorates major Islamic religious holidays such as the birthday of the Prophet and Isro'mi'roj of the great Prophet Muhammad SAW by bringing in Ustad and/or motivators from outside. Philosophically, it plays a very important role in forming students' moral, cultured, wise and more critical character, behavior, habits, preferences, abilities, talents, potential, values ​​and finally patterns of thinking. From an educational psychology perspective, it can help students overcome these challenges and build positive characters such as working together with other people. Students must learn to work in teams and collaborate with others in completing assignments. Sociologically, students interact with teachers and students, class group dynamics and intra-school organization